2023
DOI: 10.1037/adb0000906
|View full text |Cite
|
Sign up to set email alerts
|

Reaching out to big losers: Exploring intervention effects using individualized follow-up.

Abstract: Objective: Previous research suggests that a brief duty-of-care telephone call to high expenditure customers was associated with lower gambling over the subsequent year. The current aim was to assess effects on individual trajectories rather than overall group effects reported previously. The objective was to identify different patterns of individual change over the follow-up year and explore differential responses of subgroups of individuals. Method: A matched pair design contrasting the outcome for telephone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Sweden [79] and the UK [55]. These Norwegian studies have found evidence in support of safer gambling features within on-line operators' platforms [76,77] as well as evidence for an individualized telephone call intervention for higher-spending gamblers [47], which has revealed persistent effects at a year's follow-up [80]. As gambling supply is restricted to so few operators in Norway, it is also fairly straightforward for researchers to derive relatively universal measures of gambling behaviour to study responses to these interventions.…”
Section: Evaluating Harm-reduction Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Sweden [79] and the UK [55]. These Norwegian studies have found evidence in support of safer gambling features within on-line operators' platforms [76,77] as well as evidence for an individualized telephone call intervention for higher-spending gamblers [47], which has revealed persistent effects at a year's follow-up [80]. As gambling supply is restricted to so few operators in Norway, it is also fairly straightforward for researchers to derive relatively universal measures of gambling behaviour to study responses to these interventions.…”
Section: Evaluating Harm-reduction Measuresmentioning
confidence: 99%
“…Such conflicts between researchers and commercial gambling operators may explain why field studies involving collaborations with the Norwegian state monopolies have asked some of the more impactful research questions to date [47,76,77], with some notable field studies also having recently been conducted in Australia [78], Sweden [79] and the UK [55]. These Norwegian studies have found evidence in support of safer gambling features within on‐line operators’ platforms [76,77] as well as evidence for an individualized telephone call intervention for higher‐spending gamblers [47], which has revealed persistent effects at a year's follow‐up [80]. As gambling supply is restricted to so few operators in Norway, it is also fairly straightforward for researchers to derive relatively universal measures of gambling behaviour to study responses to these interventions.…”
Section: Evaluating Harm‐reduction Measuresmentioning
confidence: 99%